Adolescent attitudes toward police and crime reporting intentions - Burden, Makayla (Journal of crime and justice, 2023)
Positive interactions with police among youth can help establish long-lasting positive attitudes toward police (ATP). A particularly important aspect of the relationship between juveniles and the police is their willingness to report crime to law enforcement. Unfortunately, many adolescent victimizations go unreported. We used a sample of 5th and 6th grade students (N = 1,994) in two separate cohorts from two independent data collection intervals of a large-scale study in a Midwestern county to examine how early adolescent ATP, and other factors, such as demographic characteristics, delinquency involvement, prior victimization, fear of victimization, and the perceived risk of victimization, influences intentions to report crime to the police. Results indicated that students in both cohorts who had more positive ATP and a greater perceived risk of victimization reported greater intentions to report crimes to the police. Additionally, White students reported greater willingness to report to the police than Black students. Other results varied between the two cohorts. Implications for the association between ATP and willingness to report to the police are discussed.